Penerapan Labelisasi Halal pada Rumah Makan dan Restoran di Kota Padang dalam Pengembangan Pariwisata - Nazar, Jasman (Pagaruyuang Law Journal, 2019)
This research tries to examine and discuss about The Regulation and Implementation of the Standardization and Certification of Tourism Business Services in Padang City that will answer some problems, they are, how the implementation of standardization and certification regulation of tourism business services in Padang and what efforts that is being done by the government to give protection to the tourist. This is a descriptive study using an empirical juridical method. After doing research, some answers that can be conclude, Padang has not done the standardization and certification of tourism business services. And to protect the tourist the government implements some obligations that must be fulfilled by the businessmen about the services they given, perform guidance of tourism awareness to the society and also work together with the Tourism organization and constabulary in city of Padang.